2013
DOI: 10.1103/physrevb.87.155310
|View full text |Cite
|
Sign up to set email alerts
|

Epilayer thickness and strain dependence of Ge(113) surface energies

Abstract: The stability and growth of three-dimensional (3D) nanostructures in the Ge on Si system is controlled in part by the strain-and overlayer-thickness-dependent surface energies of the crystal facets involved. Here, we use density functional theory (DFT) with local-density approximation calculations to calculate the strain-and thickness-dependent energy of various Ge(113) and Si(113) surface reconstructions. Results of DFT calculations are compared to Tersoff potential calculations to assess the relative importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…The surface energy density of Ge (001) is about 6.1 eV/nm 2 [37]. As for the {1 1 3} facets, the key parameters of Ge {1 1 3} surface energies are adopted from the recent progress in ab initio calculation [38]. It should be noted that although the strain energy calculations are done with the Ge concentration being set to 20%, surface parameters for pure Ge {1 0 5}, (0 0 1), and {1 1 3} facets are adopted due to the dominating Ge surface segregation observed in previous studies [9, 14, 39].…”
Section: Resultsmentioning
confidence: 99%
“…The surface energy density of Ge (001) is about 6.1 eV/nm 2 [37]. As for the {1 1 3} facets, the key parameters of Ge {1 1 3} surface energies are adopted from the recent progress in ab initio calculation [38]. It should be noted that although the strain energy calculations are done with the Ge concentration being set to 20%, surface parameters for pure Ge {1 0 5}, (0 0 1), and {1 1 3} facets are adopted due to the dominating Ge surface segregation observed in previous studies [9, 14, 39].…”
Section: Resultsmentioning
confidence: 99%
“…C S  =  SV -2/3 and C B  =  BV -2/3 are shape-dependent factors which depend on the relative extension of the area of the lateral facets, S , and of the base area, B , of dots/wires. Previous results have shown that both the tensile strained Ge(113) [28] and the Ge(001) [29] surfaces have roughly the same surface energy value of about 65 meV/Å 2 ; therefore, for the sake of simplicity, we assume γ S  =  γ B  = 65 meV/Å 2 . Figure  10d shows the dependence of the total energy of dots/wires on the volume; in panel (e), their relative difference is plotted.…”
Section: Resultsmentioning
confidence: 99%
“…Because the system can be regarded as an axially symmetric problem, in the polar coordinate system, substituting Eqs. (18) and (19) into Eq. (20), one gets Then the elastic displacement can be solved as follows:…”
Section: Appendix B: Analytical Expression For Elastic Response Due Tmentioning
confidence: 99%
“…By using Eq. (18) and Eq. (19), we obtain the stress and strain components in the island and substrate as follows:…”
Section: Appendix B: Analytical Expression For Elastic Response Due Tmentioning
confidence: 99%
See 1 more Smart Citation